2017
DOI: 10.1038/s41598-017-02422-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of IL-9 induced by Schistosoma japonicum infection in C57BL/6 mouse liver

Abstract: Liver granulomatous inflammation and fibrosis were the primary pathological changes observed during Schistosoma japonicum (S. japonicum) infection. In the present study, the characteristics of IL-9 were investigated in the liver of S. japonicum infection C57BL/6 mice. Immunofluorescence, qRT-PCR, and ELISA results demonstrated that the expression of IL-9 significantly increased after infection (P < 0.01). FACS results indicated that the peak of IL-9+ Th9 cells in the liver mononuclear cells appeared at the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
3
16
1
Order By: Relevance
“…More importantly, we found that the degree of liver fibrosis was also alleviated after neutralization of IL-9. This result was consistent with the findings of Li et al, 34 but the mechanisms of IL-9 pro-fibrosis remain unknown. As the granuloma matures, fibroblasts, which lead to production of extracellular matrix and collagen fibres, were recruited at the outer zone of the granuloma, resulting in fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, we found that the degree of liver fibrosis was also alleviated after neutralization of IL-9. This result was consistent with the findings of Li et al, 34 but the mechanisms of IL-9 pro-fibrosis remain unknown. As the granuloma matures, fibroblasts, which lead to production of extracellular matrix and collagen fibres, were recruited at the outer zone of the granuloma, resulting in fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, dynamic changes of Th9, IL-9, and PU.1 levels were consistent with hepatic egg granulomatous inflammation (101). In agreement with these studies, Li et al additionally showed that anti-IL-9 monoclonal antibody treatment significantly inhibits S. japonicum-induced hepatic granulomatous and fibrosing inflammation (102). The above findings indicate that Th9 cells may be involved in immunopathogenesis in murine schistosomiasis.…”
Section: Th9 Cells and Egg-induced Hepatic Granulomatous And Fibrosissupporting
confidence: 63%
“… 56 Follicular helper T cells and Th9 cells have also been implicated in promoting egg-induced hepatic granulomas and fibrosis. 57 , 58 Thus, Th2 immunity functions like a two-edged sword, on one hand protecting the host against excessive granulomatous inflammation, and on the other, causing host immune-dependent liver damage. A balance between Th1 and Th2 responses may therefore be necessary to prevent severe pathology.…”
Section: What We Have Learnt From Experimental Animal Studiesmentioning
confidence: 99%